Pelayanan Persalinan Bidan Dan Dukun Di Desa Kuraa Kecamatan Siontapina Kabupaten Buton - Taswin Taswin; Nursiah Nursiah (Jurnal Kesehatan Indonesia, 2016)
The implementation of labor care that is not comprehensive causing many problems either labor services of midwife or traditional midwife. The objective of the research was to find out the description of labor services of midwife and traditional midwife at Kuraa village in Siontapina sub-district, Buton regency. Study design was qualitative with a phenomenological approach. Total sample was 20 respondents who consist of 10 women, 7 birth mothers, 2 traditional midwife, and 1 a midwife. Technique of taking sample was purposively. The result showed that the labor care from a midwife who started from stage I to stage IV has not been fully run in accordance with midwifery care because in laboring process, the traditional midwife who always took precedence. Whereas, in assisting childbirth, traditional midwife has not followed the midwifery care because sometimes they do not involve a midwife. Keywords: labor services, midwife, traditional midwife